Understanding the effect of revolution and rotation of the earth on prayer times using accurate times - Abu Yazid Raisal; Arwin Juli Rakhmadi (Sultang Agung Islamic University, 2020)
Prayer time is closely related to the position of the Sun toward the Earth. The position of the Sun against the Earth is affected by the revolution and rotation of the Earth. Three cities were chosen to see the effect of revolution and rotation of the Earth on prayer times in the hemisphere, namely Stockholm city representing the northern hemisphere, Wellington city representing the southern hemisphere, and Pontianak city representing the equatorial region. Prayer times are calculated using the Accurate Times software during the equinox, summer solstice, and winter solstice in 2020. Locations in high latitudes will experience large differences in prayer times throughout the year due to differences in day and night lengths. Accurate Times software can show the prayer times difference in the hemisphere. Areas that sometimes experience day for 24 hours or night for 24 hours are difficult in determining prayer times. There are two options to overcome this problem, namely adjusting to neighboring countries where night and day can be distinguished or following prayer times in Mecca and Medina.